Soil surface properties and implications for soil carbon sequestration in early-stage ecovoltaic grassland restoration - Krasner, Noah Z.; Li, Yudi; Friis, Dahlia C.; Benitez, Joaquin; Stebbins, Edward; Pinilla, Pablo; Maciel, Pablo; Thompson, Aemilia; Wong, Michael; Condon, Daphne; Lybrand, Rebecca A.; Hernandez, Rebecca R. (Frontiers in Environmental Science, 2025)
Large, ground-mounted photovoltaic solar energy (GPV) development is expanding rapidly, but its impact on soils and ecosystem services is unresolved. The co-location of ecological restoration with photovoltaic (PV) solar energy generation, known as an ecovoltaic solar park, is proposed as a nature-based climate solution to restore these ecosystem services and improve soil conditions (e.g., erosion mitigation). In this study, a GPV in the Central Valley of California, United States was partially restored with a multifunctional native grassland seed mix. We sought to characterize 13 unique soil surface properties across microsites, elucidate early effects of native grassland restoration on these properties, and compare these results with an adjacent agricultural land-use type (i.e., vineyard). Among these were important physico-mechanical properties rarely studied at GPVs, including penetration resistance, surface failure shear strength, and saturated hydraulic conductivity. Areas under PV panels showed improved penetration resistance and soil moisture relative to sun-exposed areas. Newly restored areas had moister soils, too, but little to no improvement to soil physico-mechanical properties important for vegetation establishment. However, they exhibited slightly greater, but non-significant carbon stocks (to 5 cm) than unrestored areas, and accelerated soil carbon, organic carbon, and nitrogen accrual in zones of concentrated runoff. This study demonstrates initial evidence of soil-based ecosystem services supported from restoration activities at an ecovoltaic solar park, specifically in carbon sequestration, remediation for vegetation establishment, and synergistic relationships with unique microsite conditions from fixed-tilt GPV infrastructure. Additional studies at more GPVs, over longer periods of time, with greater standardization, and those that distinguish between distinct soil C fractions are necessary to fully elucidate complex interactions between soils and GPVs, especially in ecovoltaic contexts.